2020
DOI: 10.1016/j.jad.2020.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quarantine on mental health of populations affected by Covid-19

Abstract: Highlights From a psychological perspective, citizens in a state of confinement can feel constraint and express fixation on the state of the disease. The rapid infection spread and the high number of confirmed deaths have been responsible for the symptoms of anxiety, depression and stress reported by the public and the medical team. Individuals quarantined reported negative psychological implications, such as symptoms of post-traumatic stress, confusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 9 publications
2
43
1
4
Order By: Relevance
“…Given the longer required quarantine period of COVID-19 and the similar transmission rate of 2–3% with SARS then psychological distress is likely to be higher ( Jiang et al, 2020 ). This is of particular importance as recent studies have demonstrated that prolonged confinement is associated with psychological damage and strain ( de Lima et al, 2020 ; Mazza et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the longer required quarantine period of COVID-19 and the similar transmission rate of 2–3% with SARS then psychological distress is likely to be higher ( Jiang et al, 2020 ). This is of particular importance as recent studies have demonstrated that prolonged confinement is associated with psychological damage and strain ( de Lima et al, 2020 ; Mazza et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater-Based Epidemiology (WBE) is an epidemiological tool improve predictions and assist in mitigating COVID-19 outbreaks by evaluating biomarkers in a speci c community 14 . The primary advantage is related to minimizing domino effects such as unnecessarily long stay-at-home policies that stress humans and economies alike 15 . While researchers have evaluated biomarkers for SARS-CoV-2 there is no information of how the wastewater microbiome is altered in communities infected by coronavirus or if the enteric bacteria can display species-speci c signatures detected in sewage either from symptomatic and asymptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the countries affected by the COVID-19 proceeded with all kinds of social restrictions, with quarantine being one of the most isolating and aggravating one (15,16). Its purpose is to protect the population's physical health, but it often causes the worsening of psychological well-being (17)(18)(19)(20). Being quarantined is connected with abrupt changes in daily life, mobility limitations, and disruption of social interactions, contributing to severe stress-related responses, anxiety, depression (7,8), post-traumatic stress symptoms (PTSS) (14,21), insomnia, anger, fear of being discriminated or stigmatized (16), low self-esteem, and a lack of self-control (15).…”
Section: Introductionmentioning
confidence: 99%